Sustainable Wireless Networks - Zheng, Zhongming; Cai, Lin X.; Shen, Xuemin; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2013)
This brief focuses on network planning and resource allocation by jointly considering cost and energy sustainability in wireless networks with sustainable energy. The characteristics of green energy and investigating existing energy-efficient green approaches for wireless networks with sustainable energy is covered in the first part of this brief. The book then addresses the random availability and capacity of the energy supply. The authors explore how to maximize the energy sustainability of the network and minimize the failure probability that the mesh access points (APs) could deplete their energy and put the network out of service due to the unreliable energy supply. This brief also studies network resource management issues in green wireless networks to minimize cost. It jointly considers the relay node (RN) placement and sub-carrier allocation (RNP-SA) issues in wireless networks with sustainable energy, and then formulates the problem into a mixed integer non-linear programming problem. Concise and informative, this brief is a useful resource for professionals or researchers studying wireless networks, communication networks, and energy efficiency. Advanced-level students interested in energy technology or communications engineering will also find the material valuable.
Introduction -- Background and Literature Survey -- Joint Relay Placement and Sub-carrier Allocation in Sustainable Wireless Networks -- Analysis and Resource Management for Sustainable Wireless Networks -- Conclusions and Future Directions.
Keywords: Computer science; Computer Communication Networks; Telecommunication; Production of electric energy or power; Electric engineering; Renewable energy sources; Computer Science; Computer Communication Networks; Energy Technology; Renewable and Green Energy; Communications Engineering, Networks; Power Electronics, Electrical Machines and Networks